Clinical ethics consultations in psychiatric compared to non-psychiatric medical settings: characteristics and outcomes. Issue 1 (January 2019) - Löbbing, T.; Carvalho Fernando, S.; Driessen, M.; Schulz, M.; Behrens, J.; Kobert, K.K.B.
Abstract: Background: In the recent years clinical ethics consultations (CEC) received an increasing attention not only in patients with medical conditions but also in those with mental disorders. However, the systematic and empirical knowledge is still small. The aim of this observational study was to investigate whether CECs differ between psychiatric and medical hospital inpatients regarding ethical issues, goals, characteristics, processes, and outcomes. Methods: This is a retrospective and in parts prospective analysis of a semi-structured CEC approach provided by the CEC service at a large German general hospital between January 2006 and June 2015. Results: A total of 259 CECs in three inpatient settings were investigated, i.e. intensive care units (ICU, 43.6%), low care units (LCU, 33.6%), and psychiatric care units (PCU, 22.8%). In all groups, most ethical issues addressed treatment intensity (80.6%) and resulted in over 93% in participants' agreement on final ethical recommendations as well as in high implementation rates (>89%). However, we found significant group differences: In PCUs patients participated more often in the CEC (p < .001), the number of all participants was higher (p < .001), CECs were more time expensive (p < .001), and more recommendations focused on interventions against the patients' declared intention (37.7% versus 0%) than in the other groups. Discussion: In spite of different clinical characteristics and ethical issues between patients and settings, consensus and implementation of the CEC recommendation could be achieved at a high rate in all groups. There are substantial differences regarding goals, participation of patients, and processes. It is worth considering adapting the CEC to the special needs in psychiatric settings, especially under the aspect of the patients' perspective and involvement.